2016
DOI: 10.1097/brs.0000000000001629
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study of the Six Degrees of Freedom Cervical Spine Range of Motion During Dynamic Flexion, Extension, and Rotation After Single-level Anterior Arthrodesis

Abstract: Study Design A longitudinal study using biplane radiography to measure in vivo intervertebral range of motion (ROM) during dynamic flexion/extension and rotation. Objective To longitudinally compare intervertebral maximal ROM and midrange motion in asymptomatic control subjects and single-level arthrodesis patients. Summary of Background Data In vitro studies consistently report that adjacent segment maximal ROM increases superior and inferior to cervical arthrodesis. Previous in vivo results have been con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Axial, sagittal, and coronal orientation of the subaxial cervical spine was reported to change from level to level [24]. The present study shows that the variation of facet orientation is associated with MCs dimensions at different cervical levels.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Axial, sagittal, and coronal orientation of the subaxial cervical spine was reported to change from level to level [24]. The present study shows that the variation of facet orientation is associated with MCs dimensions at different cervical levels.…”
Section: Discussionmentioning
confidence: 52%
“…Independent of age, we revealed that the subaxial cervical facet at each level showed the most vertical orientation. It is generally accepted that the rotation movements are dominated by the axial cervical spine, whereas the flexion-extension is dominated by the subaxial spine [24]. The shallowness of C3 facet joints determines mobility between 2 vertebral bodies, and vertical facets restrain the translation of the axial spine over C3.…”
Section: Discussionmentioning
confidence: 99%
“…After cervical spinal fusion, motion in the treated level is eliminated. In contrast, ranges of motion at adjacent segments generally increase in daily activities, due to the compensatory effect [7]. On the other hand, joint biomechanics is known to affect intervertebral disc degeneration [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to parameters such as range of motion or stiffness, the IHA and its migration enable the comprehension of the complex motion properties of an FSU. Although the IHA has been analyzed by different approaches, including sequential radiography, optical systems, and finite element studies (Rousseau et al 2006 , 2008 ; Dugailly et al 2010 ; Park et al 2011 ; Crawford et al 2012 ; Anderst et al 2013 , 2016 ), the 6D apparatus used in this study offers a comparably very high spatial-temporal resolution. The authors hypothesized that: (1) the location of the IHA is placed somewhere near the posterior part or even at the border of the vertebral body in the horizontal plane and (2) the resection of both FJs leads to an instability of the FSUs and a ventral shift in the locations of the IHA.…”
Section: Introductionmentioning
confidence: 99%